2015
DOI: 10.1007/s00442-015-3396-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased rainfall variability and N addition accelerate litter decomposition in a restored prairie

Abstract: Anthropogenic nitrogen deposition and projected increases in rainfall variability (the frequency of drought and heavy rainfall events) are expected to strongly influence ecosystem processes such as litter decomposition. However, how these two global change factors interact to influence litter decomposition is largely unknown. I examined how increased rainfall variability and nitrogen addition affected mass and nitrogen loss of litter from two tallgrass prairie species, Schizachyrium scoparium and Solidago cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Projections for Indiana suggest annual precipitation could increase by as much as 20% and the frequency of heavy rainfall events could increase by as much as 40% by the year 2095 (Diffenbaugh et al 2005) PRICLE was established in a tallgrass prairie restoration site; the plant community was dominated by Solidago canadensis and Schizachyrium scoparium and grew in a sandy loam soil. Consequently, seasonal maximum 5-d cumulative rainfall was increased by an average of 14% over the course of the experiment (Schuster 2016), an extent comparable to projections made by the CMIP5 climate model ensemble for the year 2100 (Sillmann et al 2013, Stocker et al 2014. PRICLE was initiated during May 2012 (2 yr prior to the start of this experiment) and consisted of three blocks of four plots (each 4 9 5.5 m) exposed to a factorial combination of IRV (or ambient control) and N addition (or ambient control).…”
Section: The Prairie Invasion and Climate Experiments (Pricle)supporting
confidence: 70%
See 2 more Smart Citations
“…Projections for Indiana suggest annual precipitation could increase by as much as 20% and the frequency of heavy rainfall events could increase by as much as 40% by the year 2095 (Diffenbaugh et al 2005) PRICLE was established in a tallgrass prairie restoration site; the plant community was dominated by Solidago canadensis and Schizachyrium scoparium and grew in a sandy loam soil. Consequently, seasonal maximum 5-d cumulative rainfall was increased by an average of 14% over the course of the experiment (Schuster 2016), an extent comparable to projections made by the CMIP5 climate model ensemble for the year 2100 (Sillmann et al 2013, Stocker et al 2014. PRICLE was initiated during May 2012 (2 yr prior to the start of this experiment) and consisted of three blocks of four plots (each 4 9 5.5 m) exposed to a factorial combination of IRV (or ambient control) and N addition (or ambient control).…”
Section: The Prairie Invasion and Climate Experiments (Pricle)supporting
confidence: 70%
“…Thus, all plots received the same amount of "rainfall" over the course of the growing season, but those under partial rain-out shelters experienced a more variable rainfall regime wherein half of all rainfall was consolidated into a five large events each growing season. Consequently, seasonal maximum 5-d cumulative rainfall was increased by an average of 14% over the course of the experiment (Schuster 2016), an extent comparable to projections made by the CMIP5 climate model ensemble for the year 2100 (Sillmann et al 2013, Stocker et al 2014. In order to control for shading effects of the rainout shelters, we placed similar structures covered in wildlife netting instead of polycarbonate over ambient rainfall plots.…”
Section: The Prairie Invasion and Climate Experiments (Pricle)supporting
confidence: 70%
See 1 more Smart Citation
“…We conducted this research near West Lafayette, Indiana, USA, within the Prairie Invasion and Climate Experiment (PRICLE; Schuster ), a fully factorial global change experiment with two levels of rainfall variability (ambient and added) and two levels of N addition (control and +5 g N m −2 year −1 ). PRICLE is located within a restored tallgrass prairie established on a sandy loam soil (66% sand, 24% silt, 10% clay) at the Purdue Wildlife Area (40·4°N 86·9°W).…”
Section: Methodsmentioning
confidence: 99%
“…An uptrend in the continuous emissions of N has been reported in China since the 1980s (Zhang et al, 2007), causing China (especially southern China) to be the third largest N deposition area in the world, followed by Europe and the United States (Galloway et al, 2004). Numerous studies have shown that the N addition can change the soil microbial community (Wang et al, 2015;Zhang et al, 2017a), accelerate litter decomposition (Schuster, 2015;Zhang et al, 2017b) and reduce plant diversity (Zeng et al, 2016;Zhang et al, 2017a). All these factors have been found to affect the structure and the function of forest ecosystems (Bobbink et al, 2010), and hence to influence BVOC fluxes from forest floor (Carriero et al, 2016;Kivimäenpää et al, 2016).…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%